2017
DOI: 10.1016/j.heliyon.2017.e00329
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties in crumple-formed paper derived materials subjected to compression

Abstract: The crumpling of precursor materials to form dense three dimensional geometries offers an attractive route towards the utilisation of minor-value waste materials. Crumple-forming results in a mesostructured system in which mechanical properties of the material are governed by complex cross-scale deformation mechanisms. Here we investigate the physical and mechanical properties of dense compacted structures fabricated by the confined uniaxial compression of a cellulose tissue to yield crumpled mesostructuring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…True stress-true strain curves from high strain-rate compression tests showed that both yield strength and peak stress levels are higher than those observed in the quasi static test; however, the endocarp becomes less ductile. This is the typical strength-ductility trade-off mechanism observed in other materials deformed at high strain rates 53 . These results clearly show a strain-rate dependence of the fruit shell, which may be explained by the strain rate sensitivity of cell material due to viscosity and by localized deformation resulting in subsequent hardening and less ductility.…”
Section: Discussionmentioning
confidence: 54%
“…True stress-true strain curves from high strain-rate compression tests showed that both yield strength and peak stress levels are higher than those observed in the quasi static test; however, the endocarp becomes less ductile. This is the typical strength-ductility trade-off mechanism observed in other materials deformed at high strain rates 53 . These results clearly show a strain-rate dependence of the fruit shell, which may be explained by the strain rate sensitivity of cell material due to viscosity and by localized deformation resulting in subsequent hardening and less ductility.…”
Section: Discussionmentioning
confidence: 54%
“…During processing, the surface under variable angle flushing of the working zone is not often sufficient and the retained debris hampers the processing, reduces the processing speed, and leads to short circuits. Another big challenge for EDM can be cutting a workpiece with an uneven structure such as a set of hollow tubes or foam-like material or material with varying mesostructure even from the known conductive and easy-to-machine (by EDM) material [31, 32].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The microtextures may mainly impact the subsequent relaxation of film structure at the micro- or macroscale, resulting in the retardation of release. Arc-shaped or corrugated surfaces have been approved to be crack-resistant due to a more efficient energy dissipation and interfacial adhesion. It is possible that microtextured fragments inside the films also undergo a similar process where the internal expansion is constrained due to enhanced interlocking and adhesion. Overall, the engineering of microtexture provides an additional and independent way to control rates without altering film composition, the intercalated molecular agent, or fluid medium.…”
Section: Resultsmentioning
confidence: 99%